The Effect Of Counterpressure Birth Ball On The Reduction Of Labor Pain In Bpm Maiharti Kisaran Barat In 2022 - Yurizki Telova (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Childbirth is a natural process that every pregnant woman will experience. Labor is defined as the stretching and dilation of the cervix due to contraction of the uterine muscles to promote the expulsion of conception. The labor experienced was a painful, most maternity mothers began to feel the peak of pain in the first stage of the active phase, namely in the maximal dilatation phase and deceleration phase. , and strong so that the sensation of pain felt increased by HIS and the opening of labor affected the pain felt by the mother. The more intense the HIS and the bigger the opening, the stronger the pain, so it requires birthball exercises as a decrease in labor pain scale during pregnancy, Counterpressure is a massage by placing the heel of the hand or the flat part of the hand, massaged 20 minutes every hour during labor will be more free from pain, can manage fear, create a feeling of comfort, relax and respond positively, Birth ball is a physical therapy ball that helps mothers in the first stage of labor to kneel and lean on the birthball can reduce pain so that mothers are more comfortable . When the birthing adjust the position, control anxiety and have a birth attendant who can divert her mind from the perception of pain, the pain will decrease. So the combination of Counterpressure Birth Ball is very important for pregnant women to learn when they want to give birth.